Flouting the Maxim of Quality in Steve Harvey’s Talk Show: a Pragmatic Analysis - Wulan Maudina; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2026)
This research conducts a pragmatic analysis of the flouting of the Maxim of Quality in the episode “Millennial Has to be Joking with This Question!” from the Steve Harvey Talk Show on the YouTube channel Steve TV Show. Pragmatic research that flouts the Maxim of Quality in the context of talk shows with millennial audiences or participants remains relatively rare. Several previous studies analyse violations of maxims in popular and more formal talk shows. However, it is not the same as on the Steve Harvey talk show, which highlights humour from flouting maxims across generations. Flouting of maxims is common in many television shows, which can certainly affect communication dynamics. This research uses Paul Grice’s Cooperative Principle and Attardo’s humour theory in the context of talk shows across generations. This research identifies and examines the actions in which Steve Harvey deliberately flouts the Maxim of Quality through strategies such as hyperbole, metaphor, irony, sarcasm, and banter. The analysis shows that hyperbole is the most commonly used strategy, followed by metaphor, banter, irony, and sarcasm. These strategies particularly serve to create humour, deliver criticism, and foster a sense of connection with the audience or build solidarity, with humour being the most significant function for this research. Thus, this study highlights how flouting the maxim of quality serves as a strategy for critical humour and can reflect social values and generational differences. Findings from research on flouting the maxim of quality and humour strategies can be used by various groups who need a deeper understanding of how to deliver messages effectively to cross-generational audiences.